"Чужий серед чужих" у п’єсі Джорджа Риги "Лист до мого сина" - Шадріна, Тетяна Володимирівна; Shadrina, T. V. (My University, 2023)
У статті розглядаються стратегії реалізації дихотомії «свій/чужий» у п’єсі канадського автора українського походження Дж. Риги «Лист до мого сина» крізь призму формування етнокультурної ідентичності. The article examines the strategies of implementing the dichotomy “own/foreign” in the play “A Letter to My Son” by the Canadian author of Ukrainian origin, J. Ryga, through the prism of the formation of ethno-cultural identity.
“A stranger among strangers” in George Riga’s play “A letter to my son”
Keywords: свій; чужий; інший; постколоніальний досвід; імагологія; ідентифікація; хронотоп; простір; мультикультуралізм; own; foreign; other; postcolonial experience; imagology; identification; chronotope; space; multiculturalism